Association of tcf7l2 variants with type 2 diabetes mellitus susceptibility and treatment outcome in a multi-ethnic Malaysian population / Muhammad Huzaimi Bin Haron - Muhammad Huzaimi, Haron (2012)
Type 2 diabetes mellitus (T2DM) is a multifactorial disease, where a combination of risk factors interacts and plays different roles, culminating in the disease proper. One such risk factor is genetics. Single nucleotide polymorphisms (SNPs) in several genes have been implicated in rising T2DM risk; one such gene is the transcription factor 7-like-2 (TCF7L2), which has been showed to blunt incretin action (specifically glucagon-like peptide-1, GLP-1), leading to impaired glucose-induced insulin secretion. Furthermore, these SNPs were also associated with an impaired therapeutic response to the sulfonylurea group of oral antidiabetic agents. To date, there is only one small scale study that looked at the effect of SNPs in TCF7L2 on T2DM in a Malaysian population, and no studies looking at the effect of these SNPs on therapeutic response to any antidiabetic agent in T2DM subjects. Our study attempted to address these deficiencies. A total of 1008 subjects comprising of 642 T2DM and 366 non-T2DM subjects, who fulfilled the inclusion and exclusion criteria, gave written informed consent to be included in this cross-sectional case-control study. Five SNPs in TCF7L2 (rs7903146, rs12255372, rs11196205, rs7901605 and rs4506565) were genotyped from peripheral leukocytes of the subjects using TaqMan SNP genotyping assays on a real-time PCR platform. Anthropometric and treatment data were obtained from interviews and medical records. Glycated haemoglobin levels were measured in the T2DM subjects. All data were analysed using IBM SPSS Statistics (version 19) and Haploview (version 4.2) softwares. This study showed that in a Malaysian population, the variant alleles of the SNPs examined were significantly more common in T2DM compared to non-T2DM subjects. The strongest association was observed in rs4506565 (p=5e-4; OR 1.97, CI 1.35 – 2.88). The haplotype TT containing both variant alleles of rs4506565 and rs7903146 were significantly more common in the T2DM subjects (p=9.97e-5; OR 1.98, CI 1.41 – 2.84). A significantly higher mean HbA1c was observed in patients on insulin therapies (alone or with oral medications) carrying the TT genotype of rs4506565. In a subset of subjects on a combination of metformin and a sulfonylurea drug, there were significantly higher mean HbA1c values in heterozygous genotype carriers of rs7903146, rs11196205, rs7901695 and rs4506565. In the same subset, heterozygous genotype carriers of rs11196205, rs7901695 and rs4506565 were associated independently with failure to achieve HbA1c target of 6.5%. TCF7L2 and T2DM in Malaysia | Abstract iii In conclusion, TCF7L2 gene polymorphism is associated with T2DM in a Malaysian population. Furthermore, carriers of the variant alleles are associated with higher HbA1c levels, which could indicate more severe disease.